Identification and Classification of Effective Operational Plans on Sustainable Production Using Repertory Grid and Principal Component Analysis: A Case Study on Industrial Production Companies in Semnan Province, Iran - Shariat, Mohammad Ali; Iranzadeh, Soleyman; Zendeh, Alireza Bafandeh (International Journal of Economics and Financial Issues, 2017)
Attenuation of natural resources, climate changes, environmental pollution, ecological incompatibility of industrial activities with the environment, and decrease in quality of human’s life due to the acceleration of global industrialization are critical factors intensively pushed production to resist against the problems while keep its competitiveness. In this regard, sustainability and, especially for production, moving towards sustainable production in order to respond to challenges that industrial countries may be encountered with in this route are of significant importance. Sustainability is an increasingly important necessity for human activities and making a sustainable development is a key goal of human development. Sustainable development is an approach targeting various social, economic and environmental issues, generally and simultaneously, in the development process. The concept of sustainable production, which is closely related to the concept of sustainable development, targets the production companies and service providers. The current paper is focused on sustainability of productive businesses and aims to identify the structures of sustainable production and to evaluate and classify more effective plans in this field. In this regard, the dimensions and structures of sustainable production were identified using interview and repertory grid method through the viewpoints of the managers of 33 successful industrial production companies with at least 5 years continuous and sustainable activity in Semnan province, Iran. Based on the interviews, 33 individual repertory grids and 175 primary individual structures of sustainable production were created. After analyzing these structures, the aggregated grid of sustainable production including 87 secondary structures was drawn. In the next step, Principal Component Analysis (PCA) was used to divide the major structures which have more important roles for achieving sustainable production into two groups and to identify their components. Keywords: Principal Component Analysis, Sustainable Production, Repertory Grid, Personal Structure Theory JEL Classifications: Q56, E3